A case for pipelining water distribution in the Narmada Irrigation System in Gujarat, India - Shah, Tushaar; Krishnan, S.; Hemant, P.; Verma, S.; Chandra, A.; Sudhir, C. (International Water Management Institute, 2010)
Thanks to farmers? resistance to provide land for constructing watercourses below the outlets, India?s famous Sardar Sarovar Project is stuck in an impasse. Against a potential to serve 1.8 million hectares, the Project was irrigating just 100,000 hectares five years after the dam and main canals were ready. Indications are that full project benefits will get delayed by years, even decades. In this paper, IWMI researchers advance ten reasons why the Project should abandon its original plan of constructing open channels and license private service providers to invest in pumps and buried pipeline networks to sell irrigation service to farmers.